Deciphering Financial Strategy Management: Insights into Performance and Investment Decision-Making - Yulianah, Yulianah (Magister Manajemen Universitas Yapis Papua, 2024)
This study explores financial strategy management's implications on organizational performance and investment decision-making processes. Employing a qualitative approach, the research conducts a comprehensive literature review to synthesize existing knowledge. The study highlights the significance of effective financial strategy management in enhancing organizational profitability, liquidity, and growth prospects. Through an analysis of empirical studies by Graham and Harvey (2001), Fama and French (1993), and Carhart (1997), the research underscores the importance of tailored financial strategies and active portfolio management in achieving superior investment performance. Furthermore, integrating environmental, social, and governance (ESG) criteria into financial strategy formulation is examined, drawing on research by Li and Tang (2020), which suggests that companies embracing sustainability principles can achieve competitive advantages and attract socially responsible investors. The findings emphasize the multifaceted nature of financial strategy management, necessitating a comprehensive understanding of internal and external factors influencing financial decisions. The study also discusses future research directions, including exploring emerging trends such as digitalization, the role of behavioral biases in financial decision-making, and longitudinal studies tracking the performance of financial strategies over time. This research contributes to the theoretical understanding and practical implications of financial strategy management in navigating dynamic market environments.